Self-assembled/composited lignin colloids utilizing for therapy, cosmetics and emulsification - Bai, Yating; Wang, Xing; Wang, Xinru; Yang, Xujie; Li, Xinke; Xin, Hanwen; Sun, Dayin; Zhou, Jinghui (Frontiers in Chemistry, 2022)
Lignin, the most abundant source of renewable aromatic compounds on the planet, is attracting more scholarly attention due to its possibility of replacing petroleum-based chemicals and products. However, it remains underutilized because of the heterogeneity of its multi-level structure that prevents homogenization and standardization of derived products. The key to solving these problems lies in finding a general preparation method to achieve the integrated utilization of lignin molecules at all levels. The assembly-mediated granulation methods provide a significant means for the integrated value-added utilization of lignin, and for biomass productization applications, it is significant to understand the molecular mechanisms of lignin nano-colloids (LNCs) formation thus accurately guiding their functionalization. Therefore, a thorough understanding of the assembly morphology and behavior of lignin in different solutions towards colloids is of great scientific importance. In this minireview, we focus on the assembly behavior of lignin in different solvents, specifically in mono-solvent and multi-solvent, and in particular, we review various methods for preparing lignin composite colloids and concentrate on the applications in therapy, cosmetics and emulsification, which are important for guiding the preparation and efficient utilization of LNCs.